2021
DOI: 10.3390/ijms22052387
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor ChbZIP1 from Alkaliphilic Microalgae Chlorella sp. BLD Enhancing Alkaline Tolerance in Transgenic Arabidopsis thaliana

Abstract: Saline-alkali soil has become an important environmental problem for crop productivity. One of the most effective approaches is to cultivate new stress-tolerant plants through genetic engineering. Through RNA-seq analysis and RT-PCR validation, a novel bZIP transcription factor ChbZIP1, which is significantly upregulated at alkali conditions, was obtained from alkaliphilic microalgae Chlorella sp. BLD. Overexpression of ChbZIP1 in Saccharomyces cerevisiae and Arabidopsis increased their alkali resistance, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…It has been reported that GBF1 , the homolog in A. thaliana , was a negative regulator of blue light-dependent hypocotyl expansion ( Gangappa et al, 2013 ) and can trigger ROS accumulation ( Giri et al, 2017 , 1). ChbZIP1 that belongs to the G subfamily may enhance antioxidation by regulating genes related to oxidant detoxification in Alkaliphilic Microalgae Chlorella to adapt to abiotic stress ( Qu et al, 2021 ). These results suggested that the G subfamily of GubZIPs may respond to pathogen invasion and environmental stress factors by regulating the accumulation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GBF1 , the homolog in A. thaliana , was a negative regulator of blue light-dependent hypocotyl expansion ( Gangappa et al, 2013 ) and can trigger ROS accumulation ( Giri et al, 2017 , 1). ChbZIP1 that belongs to the G subfamily may enhance antioxidation by regulating genes related to oxidant detoxification in Alkaliphilic Microalgae Chlorella to adapt to abiotic stress ( Qu et al, 2021 ). These results suggested that the G subfamily of GubZIPs may respond to pathogen invasion and environmental stress factors by regulating the accumulation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…BLD has been reported to increase the alkali resistance of plants. Overexpression of ChbZIP1 in Arabidopsis showed that ChbZIP1 can enhance plant adaptation to alkali stress through the active oxygen detoxification pathway, suggesting its promising potential in genetically improving plant tolerance to alkali stress (Qu et al, 2021). bZIP transcription factors are similar to MYB/MYC transcription factors in terms of their regulation, participation in ABA-dependent pathway signal transduction, and perception of stress signals to regulate gene expression.…”
Section: Induction Of Transcription Factor Expressionmentioning
confidence: 99%
“…We constructed a large-scale screening system with rice seedlings by 140 mM Na-HCO 3 (pH 9.20) treatment [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] in a greenhouse. The large-scale screening system was constructed by modifying the method of Bado et al (2020) [ 50 ] ( Figure S1A–D ).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, most reported CSAS tolerance mechanisms in plants are similar to salt stress or alkali stress tolerance mechanisms, such as accumulating organic acids to bring down the pH around the roots and inhibit the precipitation of metal ions and phosphate [ 4 , 5 ], accumulating more osmolytes (proline, soluble sugars, betaine and soluble proteins) to adjust osmosis balance [ 6 ], increasing the activity of antioxidant enzymes (catalase, superoxide dismutase, peroxidase and ascorbate peroxidase) to detoxify reactive oxygen species (ROS) [ 6 , 7 , 8 ], and regulating stomatal closure through ABA-induced pathway [ 9 , 10 ]. Many related studies for saline–alkali stress are performed using NaHCO 3 stress on the species including Salix linearistipularis , Chlorella vulgaris , Arabidopsis thaliana , Glycine soja and Medicago sativa [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. However, quite a few studies were focused on CSAS in monocots such as Puccinellia tenuiflora , sorghum and rice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%